2016
DOI: 10.2174/0929866523666160511150907
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Lysine-Linked Magainin 2 with Increased Activity Against Multidrug-Resistant Bacteria

Abstract: Due to the growing problem of antibiotic-resistant microorganisms, the development of novel antimicrobial agents is a very important challenge. Dimerization of cationic antimicrobial peptides (cAMPs) is a potential strategy for enhancing antimicrobial activity. Here, we studied the effects of magainin 2 (MG2) dimerization on its structure and biological activity. Lysine and glutamic acid were used to synthesize the C- and N-terminal dimers of MG2, respectively, in order to evaluate the impact of linker positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
3
12
0
1
Order By: Relevance
“…These findings are in line with increased membrane-perturbing properties of larger peptide aggregates (illustrated in Fig. 4.6ac) (Dempsey et al 2003;Lorenzon et al 2016;Verly et al 2017).…”
Section: Dimers Of Antimicrobial Peptidessupporting
confidence: 78%
See 1 more Smart Citation
“…These findings are in line with increased membrane-perturbing properties of larger peptide aggregates (illustrated in Fig. 4.6ac) (Dempsey et al 2003;Lorenzon et al 2016;Verly et al 2017).…”
Section: Dimers Of Antimicrobial Peptidessupporting
confidence: 78%
“…In combination with magainin monomers, the dimer stabilizes the pore formation in egg-PG membranes (Hara et al 2001). Notably whereas a dimer linked through a carboxy-terminal lysine extension was consider-ably more active than the monomer, the aminoterminal linkage through glutamic acid has no effect (Lorenzon et al 2016).…”
Section: Dimers Of Antimicrobial Peptidesmentioning
confidence: 96%
“…MG2 is one of the first AMP described [9] and might be the most studied, whose bactericidal activity arises from leakage of cell contents via pores formed by the peptides [37][38][39]. Attempts to increase antimicrobial activity have been made with MG2 analogues [40][41][42][43], especially dimers [24,44,45]. The dimeric peptide (MG2) 2 K with a lysine residue as a linker, for instance, showed the highest antimicrobial activity among disulfide linked analogues, with faster killing of E. coli and 16-fold decrease in the minimum inhibitory concentration (MIC) [24].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we showed that C-terminal dimerization of MG2 affects considerably its antimicrobial activity. The dimeric version (MG2) 2 K was up to 16 times more efficient than MG2 to kill Escherichia coli, and required a fourth of the time of the monomer to exert its antimicrobial activity [24].…”
Section: Introductionmentioning
confidence: 99%
“…Sendo a oligomerização um pré-requisito para a atividade dos PAMs, a ligação de duas moléculas para formar dímeros tem sido alvo de estudos recentes. Em alguns casos, a dimerização leva a moléculas mais ativas (47). No entanto, os efeitos desta alteração na atividade dos PAMs ainda são pouco compreendidos, pois algumas versões diméricas apresentaram redução de atividade antimicrobiana ou aumento de toxicidade.…”
unclassified